Toward an optimal sampling protocol for Hemiptera on understorey plants - Majer, Jonathan; Moir, Melinda; Brennan, Karl (2005)
There are no standardised sampling protocols for inventorying Hemiptera from understorey or canopy plants. This paper proposes an optimal protocol for the understorey, after evaluating the efficiency of seven methods to maximise the richness of Hemiptera collected from plants with minimal field and laboratory time. The methods evaluated were beating, chemical knockdown, sweeping, branch clipping, hand collecting, vacuum sampling and sticky trapping. These techniques were tested at two spatial scales: 1 ha sites and individual plants. In addition, because efficiency may differ with vegetation structure, sampling of sites was conducted in three disparate understorey habitats, and sampling of individual plants was conducted across 33 plant species. No single method sampled the majority of hemipteran species in the understorey. Chemical knockdown, vacuum sampling and beating yielded speciose samples (61, 61 and 30 species, respectively, representing 53, 53 and 26% of total species collected).